Comparative Analysis of BNI Mobile Banking and Wondr by BNI Application Performance (Study on BNI Customers in Surabaya) - Ais Mariya Ulva; R. Yuniardi Rusdianto (Publik : (Jurnal Ilmu Administrasi), 2025)
Mobile banking is a digital service that allows customers to conveniently access various banking features via mobile devices, such as checking balances, transferring funds, paying bills, and conducting other financial transactions. As technology advances, the quality of mobile banking services has become a key factor in enhancing user satisfaction and loyalty. This study aims to analyze and compare the performance of two mobile banking applications owned by Bank Negara Indonesia, namely BNI Mobile Banking and Wondr by BNI, based on user perceptions. This study employs a quantitative approach using a comparative method to identify performance differences between the two applications. Sampling was conducted using non-probability sampling, with a sample size of 160 respondents who are active users of both applications. The collected data was then analyzed using an Independent Sample T-Test to determine the differences in the means of each variable under study The results of the study indicate that there are significant differences across six key variables: ease of use, transaction speed, design, security, information content, and customer support service. Based on a comparison of average scores, the Wondr by BNI app demonstrated superior performance compared to BNI Mobile Banking. This indicates that users tend to be more satisfied with Wondr by BNI, in terms of ease of use, transaction speed, a more attractive interface, higher security, the quality of information provided, and more responsive customer support. Thus, the results of this study are expected to serve as evaluation material for app developers in improving the quality of mobile banking services to better align with the needs and expectations of users in today’s digital era.